Knowledge, Attitude, and Practice of Health Care Workers in the Management of Peptic Ulcer at the Paul VI and the Bogodogo District Hospitals, in Burkina Faso - Eric Nagaonlé Somé; Issaka Zongo; Alice Nanelin Guinganné; Estelle Congo; Maxime Koiné Drabo; Roger Sombié (Masters Program in Public Health, 2022)
Background: In 2015, peptic ulcer disease (PUD) was cause of 52.3% and 17% of digestive bleeding and death in respectively among in-hospital patients at the gastroenterology units of the main hospital in Ouagadougou. We aimed to assess the knowledge, attitudes and practices of the health care workers in the management of PUD.Subjects dan Method: It was a descriptive cross-sectional study with a prospective data collection implemented at the Paul VI and the Bogodogo District Hospitals in Ouagadougou (Burkina Faso) from December 15, 2015 to January 25, 2016. A questionnaire was administered to 134 health care workers including medical doctors, nurses and midwives.Results: The mean age was 33 years (Mean= 33.6; SD= 5.84). Females represented 61.9%. Knowledge levels were good to excellent for general knowledge, symptoms and treatment of PUD. Depending on the agent's qualification, knowledge levels were excellent in all areas for two-thirds to three-quarters of the general practitioners, except for knowledge of additional investigation analyses, where only 47.8% had an excellent knowledge. Depending on the level of education, the level of knowledge was at least good for more than 50% of the agents except for the knowledge of additional investigation analyses where only 45.2 % of the agents of secondary school level had a good knowledge. The main attitudes consisted in managing the patients in emergency and out of an emergency context in 45.8% and 42.2% of the cases, respectively. Regarding the practices, 51.5% of the HCWs systematically requested investigation analyses before starting an aetiological therapy.Conclusion: The PUD knowledge ranks from good to excellent. However, the frequent prescription of symptomatic treatments could be the cause of many complications. The promotion of continuous medical education is a good mitigation plan to resolve the issues of knowledge and competence regarding the PUD. Keywords: attitude, knowledge, peptic ulcer disease, practice Correspondence:Eric Nagaonlé Somé. Institut de Recherche en Sciences de la Santé (IRSS)/CNRST 10 BP 250 Ouagadougou 10 Burkina Faso. Email: eric.some@gmail.com. Mobile phone: +22670751333.